Contestations of memory in Southeast Asia - Kwok, Kian Woon; Waterson, Roxana (NUS Press, 2012)
Contestations of Memory in Southeast Asia applies a new theoretical literature on social memory to remembered eveents in Burma, Laos, Vietnam, Malaysia, Singapore, the Philippines and Indonesia. Highlighting connections between theorizing based on European examples and unresolved memory issues in East and Southeast Asia, the authors show how comparative study of the interpenetration of politics and lived bodily experience, of communal and personal memories, and of dominant and suppressed narratives, can yield insights into the human potential to become either perpetrators, victims or bystanders. The memories found within different groups in any society are open to negotiation, suppression, contestation, or revision in the ever-evolving politics of the present. The searching and close-grained analyses of contemporary issues found in the volume vividly illustrate the essentially plural and multivocal nature of social memories, and demonstrate the intricate connection between transnational, national and sub-national politics. Readers seeking a more nuanced and complex understanding of the past and of its continued relevance to the present and future, will find here much food for thought.